Size of interlocking nails used in the treatment of diaphyseal femoral fractures - Tan, W.J.; Kwan, Mun Keong; Deepak, A.S.; Saw, A.; Peng, B.C.; Jalalullah, W. (Malaysian Medical Association, 2006)
Fracture of the femur is most commonly treated with interlocking nailing. We conducted this study to describe and analyze the size of femoral interlocking nails used in our local population. This is a retrospective study on reamed intramedullary interlocking nailing procedures performed between 1st July 1998 and 30th June 2003. Demographic data, the diameter and length of femoral nails used were obtained from patient's medical record. A total of 267 procedures were included. The most common diameter used was 10 mm (56.9), followed by 11 mm (27.0) and 12 mm (13.1). Only 2.6 of the nails were less than 10 mm in diameter. The most common nail length was 38 cm (31.1), followed by 36 cm (24.9) and 40 cm (19.5). The longest nail used was 46 cm while the shortest 32 cm. The most commonly used femoral nails were of 10 mm diameter with the length ranging from 36 to 40 cm, which is smaller than those reported in the English literature. Nails with diameter smaller than 10 mm were required in 2.6 of patients.